Managed pressure drilling in Malaysia - Ishak, Nur Syazana (2016)
Operators in the oil and gas industry are constantly seeking cost effective methods of drilling and producing oil and gas wells to optimize production and maximize profits. Conventional drilling methods have been overwhelmed with huge operational and financial challenges, where a considerable amount of money is spent for drilling related problems; including stuck pipe, lost circulation, and excessive mud cost. Managed pressure drilling (MPD) is the new technology that enables a driller to control bottomhole pressure in the wellbore to prevent these drilling related problems. There are different variations of MPD method are designed for different problems. MPD is achieving remarkable successes in well construction applications that have been impossible using conventional methods. In less extreme applications, the technology greatly reduces risk and improves efficiency. In both cases, it helps extend the scope of deepwater prospects around the world. Most of the hydrocarbon reservoirs in Malaysia are located offshore with increasing interest in drilling deepwater well where MPD method can be benefits. As the industry remains relatively unaware of the full spectrum of MPD benefits, this dissertation will reveal in details the two MPD techniques; constant bottomhole pressure (CBHP) and pressurized mud cap drilling (PMCD) that frequently being used in Malaysia. Readers will walk through an overview and detailed applications of both methods cover determination of pore pressure and fracture gradient, wellbore breathing detection, bullheading scenario to overcome total losses and specific mud weight design for each case history.